Dynamics of D3+ slow dissociation induced by intense ultrashort laser pulses - Gaire, B.; McKenna, J.; Zohrabi, M.; Carnes, K. D.; Esry, B. D.; Ben-Itzhak, I. (My University, 2012)
The dissociation of D3+ in intense ultrashort laser pulses is investigated using an improved coincidence three-dimensional momentum imaging method that allows clear separation of all fragmentation channels and the determination of the kinetic energy release down to zero. Our results, using 10-fs, 790-nm pulses, suggest that a large peak at low kinetic energy release is associated with the D+ + D2 dissociation channel of D3+. The most likely dissociation pathways leading to two-body breakup of D3+ are identified with additional measurements using 25-fs, 790-nm and 40-fs, 395-nm pulses. We also show that the slow D+ + D2 dissociation dynamics can be manipulated by the pulse duration.